Hélène Cixous : critical impressions - Jacobus, Lee A.; Barreca, Regina (Lit book series, 1999)
Adapted from a special issue of "Literature Interpretation Theory", this book explores one of the most significant voices in contemporary literature, approaching Cixous from the perspectives of feminist theory, materialist criticism, biographical criticism and reader-response methodologies.